Agricultural Waste. (1st October 2014) - Zhang, Panpan; Chang, Chein‐Chi; Wang, Renqing; Zhang, Shuping
Abstract : A large amount of agricultural waste was generated all over the world, which could cost many problems such as environment pollution, GHG (greenhouse gas) emission, and serious disease. A review of the literature published in 2013 on topics relating to agricultural waste issues is presented, and about 180 papers were selected. The main treatment methods of agricultural waste can be biodegradation, composing, digestion, and hydrolysis. Researchers paid more attention on the waste reuse, focusing on t he environmental friendly utilization such as producing of biofuel, construction material, active carbon, adsorbent etc. Moreover, life cycle assessment (LCA) has been applied to evaluate the economic and environmental impact widely. This review is divided into the following sections: Waste Characterization, reuse, treatment, and management.